ASEAN+3 Bond Market Guide 2018 Myanmar. (Metro Manila, Philippines Asian Development Bank, 2018)
The Republic of the Union of Myanmar began to emphasize the development of its financial and capital markets in 2008. Much has been achieved since then.There were a number of significant milestones in the Myanmar financial and capital markets in 2013, including the Central Bank of Myanmar gaining its independence by law from the then Ministry of Finance, and the passage of the Securities Exchange Law (SEL). The SEL (i) laid the foundation for the key legal framework for the securities market, (ii) established the Securities and Exchange Commission of Myanmar and the Yangon Stock Exchange, and (iii) defined market participants and their activities.
Keywords: Economics; Fiscal policy -- Myanmar; Myanmar -- Economic integration; Electronic books